Understanding endometriosis knowledge among diagnosed and symptomatically at-risk individuals in Australia - Anne Reinhardt; Amelia K. Mardon; Sarah Eitze; Hannah Adler; Danielle Howe; Michelle O’Shea; Mike Armour (npj Women's Health)
Abstract Endometriosis affects 5–14% of women and those presumed female at birth (PFAB), yet public understanding remains limited. In an online survey of 427 Australians, diagnosed individuals had better knowledge about endometriosis than those at risk but undiagnosed. In detail, at-risk individuals underestimated prevalence, consequences, and diagnostic pathways. Targeted education may improve symptom recognition and healthcare engagement, supporting earlier diagnosis and better care.